Effect of nitrogen doping on the optical bandgap and electrical conductivity of nitrogen-doped reduced graphene oxide - Witjaksono, G. (MDPI, 2021)
Graphene as a material for optoelectronic design applications has been significantly re-stricted owing to zero bandgap and non-compatible handling procedures compared with regular microelectronic ones. In this work, nitrogen-doped reduced graphene oxide (N-rGO) with tunable optical bandgap and enhanced electrical conductivity was synthesized via a microwave-assisted hydrothermal method. The properties of the synthesized N-rGO were determined using XPS, FTIR and Raman spectroscopy, UV/vis, as well as FESEM techniques. The UV/vis spectroscopic analysis confirmed the narrowness of the optical bandgap from 3.4 to 3.1, 2.5, and 2.2 eV in N-rGO samples, where N-rGO samples were synthesized with a nitrogen doping concentration of 2.80, 4.53, and 5.51 at.. Besides, an enhanced n-type electrical conductivity in N-rGO was observed in Hall effect mea-surement. The observed tunable optoelectrical characteristics of N-rGO make it a suitable material for developing future optoelectronic devices at the nanoscale. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.